Augmented reality in urban places: contested content and the duplicity of code. Issue 3 (10th August 2012) - Graham, Mark; Zook, Matthew; Boulton, Andrew
<x xml:space="preserve">Abstract</x> With the increasing prevalence of both geographically referenced information and the code through which it is regulated, digital augmentations of place will become increasingly important in everyday, lived geographies. Through two detailed explorations of 'augmented realities', this paper provides a broad overview of not only the ways that those augmented realities matter, but also the complex and often duplicitous manner that code and content can congeal in our experiences of augmented places. Because the re‐makings of our spatial experiences and interactions are increasingly influenced through the ways in which content and code are fixed, ordered, stabilised and contested, this paper places a focus on how power, as mediated through technological artefacts, code and content, helps to produce place. Specifically, it demonstrates there are four key ways in which power is manifested in augmented realities: two performed largely by social actors, distributed power and communication power; and two enacted primarily via software, code power and timeless power. The paper concludes by calling for redoubled attention to both the layerings of content and the duplicity and ephemerality of code in shaping the uneven and power‐laden practices of representations and the experiences of place augmentations in urban places.